Sparteine oxidation polymorphism: a family study. - Brøsen, K (1986)
Polymorphic oxidation of the pharmacogenetic probe drug sparteine was investigated in 35 parents and 29 siblings of 20 unrelated poor metabolizer (PM) probands. Phenotyping was carried out on the basis of metabolic ratio (MR) = sparteine/dehydrosparteines in the 12 h urine. The distribution of MR was bimodal: 47 relatives (20 siblings and 27 parents) had MR ranging from 0.22-12 and were defined as extensive metabolizers (EM) whereas MR ranged from 20-340 in nine siblings and eight parents thus defined as PM. The 20 pedigrees confirmed that poor metabolism of sparteine is inherited as an autosomal recessive character. The mean recovery of dehydrosparteines (% of dose) was 27% in 23 positively identified drug free heterozygotes compared with 37% in unrelated EM (both genotypes) (P less than 0.05) previously phenotyped. Degrees of dominance of 73% and 77% were calculated on basis of log excretion of dehydrosparteines (% of dose in 12 h urine) and log MR, respectively.